Design of a Multiagent‐Based Voltage Control System in Peer‐to‐Peer Networks for Smart Grids. Issue 1 (13th January 2014) - Rohbogner, Gregor; Fey, Simon; Benoit, Pascal; Wittwer, Christof; Christ, Andreas
Abstract Energy management in distribution grids is one of the key challenges that needs to be overcome to increase the share of fluctuating renewable energies. Current control systems for energy management mainly demonstrate centralized‐ or decentralized‐hierarchical control structures. Very few systems manifest a fully decentralized multiagent‐based control structure. Multiagent‐based control systems promise to be an advantageous approach for the future distributed energy supply system because no central control entity is necessary, which eases parameterization in case of grid topology changes, and the agents are more stable against failures and changes of control topologies. Research is necessary to prove these benefits. In this study, we introduce a design of a multiagent‐based voltage control system for low‐voltage grids. In detail we introduce cooperative decision‐making processes and software solutions that allow the agents to perceive and control their environment, the agent‐discovery and localization in different types of communication networks, agent‐to‐agent communication, and the integration of the multiagent system in existing grid‐control infrastructures. Furthermore, the study proposes how different existing technologies can be combined into an applicable multiagent‐based voltage control system: the Java/OSGi‐based OpenMUC framework allows a generic field–device interaction; peer‐to‐peer discovery and session establishment functionalities are combined with the agent communication defined by the Foundation for Intelligent Physical Agents (FIPA). The ripple control‐signal technology is applied as a fallback communication between the agent and a central grid‐control center.